Industrial Development in Nepal: Navigating Challenges and Harnessing Opportunities - Nepal, Govind (State, Society and Development: PMPD Perspectives, 2024)
Nepal’s Industrial policy has traversed through various phases. A comprehensive industrial revolution plan is imperative for fostering the prosperity and development of the nation. In this backdrop, this paper aims to present challenges and opportunities of industrial development in Nepal. Despite efforts directed to industrial development since the 1930s, Nepal has been struggling to establish a sustainable foundation for industry. Presently, Nepal is confronted with multiple problems inducing stagnation, inching deindustrialization, with the zenith of industrialization reached in the 1990s. Even with an apparent increase in the number of industries and capital investments as per company registrations, a significant portion of these registered entities remains non-operational. Moreover, structural issues within the sector, coupled with entrenched rigidities among stakeholders, have hindered its resurgence. Nevertheless, genuine commitment to investment and program implementation remains elusive. Poor investment in research & development and innovation, stagnation has exacerbated the issue. Furthermore, unclear industrial development perspectives, high production costs, interest rate volatility, inadequate trade and industrial infrastructure and insufficient backward and forward linkages, protracted registration processes, and an unpredictable investment climate collectively have impeded industrial progress. To revive industrial development, significant investment in industrial and trade infrastructure, including roads, telecommunications, and electricity should be built. Simplifying legal provisions, implementing import substitution strategies, exploring international markets, and upholding quality standards are imperative for industrial development. Commitments should be towards green industrial policies. Finally, technical interventions must be accompanied by a shift in bureaucratic and leadership mindsets.